Can plant phenolic compounds reduce Fusarium growth and mycotoxin production in cereals?. Issue 12 (2nd December 2018) - Schöneberg, Torsten; Kibler, Karin; Sulyok, Michael; Musa, Tomke; Bucheli, Thomas D.; Mascher, Fabio; Bertossa, Mario; Voegele, Ralf T.; Vogelgsang, Susanne
ABSTRACT: To assess the in vitro activity of three phenolic acids (ferulic acid, p-hydroxybenzoic acid, vanillic acid) and two flavonols (quercetin, rutin) on mycelial growth and mycotoxin accumulation of Fusarium graminearum (FG), F. langsethiae (FL) and F. poae (FP), two different approaches were chosen. First, grains from oat varieties were inoculated with a suspension of three FL isolates to determine the influence of phenolic compounds on the accumulation of mycotoxins. The oat variety Zorro showed a tendency for lower accumulation of T-2/HT-2, diacetoxyscirpenol and neosolaniol. Second, a mycelium growth assay was conducted to follow FG, FL and FP growth on cereal based media supplemented with phenolic compounds. Increasing concentrations of ferulic acid substantially inhibited growth of FG and FL, while FP growth was reduced to 57%. In contrast, p-hydroxybenzoic acid, vanillic acid, quercetin, and rutin slightly stimulated mycelium growth. Results about mycotoxin production in cereal based media were less conclusive. GRAPHICAL ABSTRACT: